Strategi Guru Pendidikan Agama Islam dalam Pencegahan dan Penanganan Bullying pada Siswa SMAN 4 Kota Bima - Jisman Jisman; Masita Masita; Khairudin Khairudin (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to provide an in-depth description of various forms of bullying behavior that occur within the school environment and sto explain the strategies implemented for its prevention and management at SMAN 4 Kota Bima. The research employs a qualitative approach with a descriptive design, focusing on obtaining a comprehensive understanding of social phenomena within the educational setting.The data sources in this study consist of teachers, students, and school administrators who are actively involved in character-building programs and efforts to address bullying cases. Data were collected through direct observation, in-depth interviews, and documentation studies, while data analysis was conducted using Miles and Huberman’s interactive model, which includes data collection, data reduction, data presentation, and conclusion drawing. The findings reveal that bullying behaviors at SMAN 4 Kota Bima include physical, verbal, and social aspects, which are primarily influenced by poor self-control, negative peer interactions, and low moral awareness among students. Prevention strategies are carried out through religious character-building programs, including lectures, counseling, and the reinforcement of religious values (IMTAQ), focusing on fostering empathy, discipline, and responsibility. Meanwhile, handling strategies are implemented through collaboration between guidance and counseling teachers, homeroom teachers, subject teachers, and parents, with actions such as personal guidance, educational sanctions, and relocation recommendations for students who show no behavioral improvement. Overall, the implementation of these strategies has proven effective in reducing bullying incidents, enhancing students’ moral awareness, and creating a safe and harmonious learning environment. Thus, the prevention and management efforts at SMAN 4 Kota Bima have contributed positively to the continuous development of students’ religious and social character.